Physiology and fertility outcomes of lactating dairy cows submitted to different resynchronization programs initiated 25 days after AI - Stolf, Rafael Luiz (2025)
The study evaluated strategies for resynchronization protocols for timed-AI (TAI) initiated 25 days after a prior insemination in lactating dairy cows. After the 1st TAI, 1,231 cows from a dairy herd were allocated, according to parity, into 2 groups for resynchronization: GnRH (G; n=595) or GnRH plus P4 device (G+P4; n=636). On d25, all cows received 16.8μg buserelin acetate (GnRH). Ultrasound assessment was performed on d32 for non-pregnant diagnostic (NPD). In G-group, cows were further categorized based on the presence of CL. Cows with CL received 0.53mg of cloprostenol (PGF) on d32, followed by a second PGF on d33, plus 1mg estradiol cypionate (EC), 300IU eCG and tail chalk for estrus evaluation. On d35, another TAI was performed. Otherwise, G-group without a CL, initiated another TAI protocol, starting with a new P4 device (2g) and 16.8 μg of GnRH. On d39, these cows received the first PGF, and 24h later the second PGF, EC, eCG were given with similar doses, concomitant with P4 withdrawal. TAI was performed on d42. In G+P4 group, all cows started the resynchronization protocol on d25 with GnRH and P4 device. On d32, in NPD (regardless of CL presence), open cows received PGF. On d33, the P4 device was withdrawn, PGF, EC, eCG was given, tail chalk was applied for estrus detection and 48h later, on d35, cows were bred. After assigned to an experimental group, cows followed the same resynchronization strategy up to the 4th service. Ultrasound evaluations were performed on d25 and d32 to record presence and number of CL, and ovulation after d25. Pregnancy per AI (P/AI) and pregnancy loss (PL; d30 to 60) of 1st AI were evaluated. The economic analysis was conducted through the development of an incremental cash flow, obtaining NPV and IRR indicators, as well as the creation of an economic model. Statistical analyses were done by logistic regression using PROC GLIMMIX (SAS 9.4; P≤0.05). Presence of CL for G and G+P4 groups on d25 (77.7 [206/265] vs 78.5% [257/308]) and d32 (85.2 [226/265] vs 83.4% [257/308]) did not differ, as well as ovulation after d25 (56.6 [150/265] vs 48.7% [150/308]) and expression of estrus (77.2 [180/233] vs 73.3% [231/315]). P/AI on d32 did not differ (43.7 [116/265] vs 40.2% [124/308] for G and G+P4, respectively). Cows that received the 1st AI or all prior services had similar fertility when submitted to G and G+P4, respectively (45.8 [151/329] vs 44.0% [148/336] and 47.7 [281/589] vs 44.3% [277/625]). PL after the 1st TAI did not differ between G and G+P4 (13.5 [20/148] vs 10.2% [15/146]), nor for the resynchronizations (15.2 [37/242] vs 10.1% [23/227]). Hormonal treatments, with the use of GnRH alone, proved relevant with an increase in cost and benefit. In conclusion, the resynch programs with all cows re-inseminated at 35 d interval (G+P4 group) or the resynch that selected cows to be inseminated on d35 or d42 (G group), with a targeted use of P4 implant resulted in similar fertility, without compromising fertility of prior AIs. Both protocols reduced the interval between inseminations, and these findings offer flexibility for farmers and technicians to choose the most appropriate, economically viable reproductive management strategy.